Community Education in The Perspective of The Quran and Hadith - Nadia Nur; Muhammad Munadi (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
The educational process occurs not only in the school environment but also in the family and community environment. As a religion that prioritizes knowledge, Islam also supports these various educational paths, including education in society. So, this research will discuss how the Islamic perspective on community education when viewed from the arguments in the Qur'an and Hadith. The method used in this paper is a literature study, namely research that uses data from library sources for further review and analysis to produce an objective conception. After the data is collected, then analyzed using content analysis techniues The results of this study are that in the Qur'an and hadith, it has been implicitly explained about community education, where the purpose of community education is ultimately to want people who are faithful and pious.